O-200 Women's understanding of their personal chance of success with IVF. (30th June 2022) - Wessels, C; Vollenhoven, B; Hammarberg, K; Lensen, S; Mol, B
Abstract: Study question: How well informed are Australian women who undergo In Vitro Fertilisation (IVF) about their treatment and their chances of having a baby? Summary answer: Only one in four women accurately estimated their individual chance of success with IVF and most women overestimated their chance. What is known already: IVF is the cornerstone of infertility treatment, and high quality, transparent and reliable treatment information is essential for patient-centred care. A recent review into IVF practice in Victoria, Australia has highlighted deficiencies in information-provision. Similar findings have also been reported internationally. An assessment of women's understanding of various aspects of the treatment is needed to identify information gaps that should be addressed by clinicians. While limited knowledge about infertility and infertility treatment in the general population is well-documented, little is known about the level of knowledge about infertility treatment among women undergoing IVF treatment. Study design, size, duration: We conducted an anonymous online survey of women who had started IVF since 2018 in Australia. The survey aimed to assess how well-informed women feel about their treatment, and was advertised on social media, enabling women from across Australia to participate. Responses were collected from 3 to 21 June 2021. Participants/materials, setting, methods: The survey included questions on demographic characteristics and IVF history. It also asked how well-informed participants felt about their treatment, what they thought their chance of having a baby from one IVF treatment cycle was, how they rated their knowledge about chance of success, and about their experience of receiving IVF-related information. Participants' beliefs about chance of success were compared with their chance as calculated by the Society for Assisted Reproductive Technology's (SART) online calculator. Main results and the role of chance: The survey was completed by 225 women. Only about a quarter (25.8%) of participants accurately estimated their chance of success within 20% relative to their SART calculated chance, and more than half (52.4%) overestimated their chance. Among women who rated their understanding of their chance of success as 'high' (7-10/10), less than one third (31.6%) accurately estimated their chance of success. Older age and having undergone several cycles were associated with women being more likely to overestimate their chance of success (odds ratios of 3.2 and 2.5, respectively). Ninety percent of women indicated that their preferred source of treatment information was a consultation with their doctor, despite many women reporting that doctors only explained the probability of having a baby with IVF moderately well (mean 5.9/10). Women also reported that they wished they had been given more realistic information about IVF and their chance of success. It is difficult to determine to what extent women's lack of understanding of what is possible with IVF is due to poor information-provision by clinicians and the clinic, and how much can be explained by optimism bias. Limitations, reasons for caution: The dissemination method precludes calculation of response rate, and it is not possible to know if participants are representative of all women undergoing IVF. There is inherent imprecision in the way understanding of chance of success was estimated. The potential impact of recall bias could neither be quantified nor excluded. Wider implications of the findings: The poor understanding of personal chance of success amongst women undergoing IVF in Australia, highlights the need for systematic and evidence-based improvement in the way clinics inform patients about the probability of having a baby with IVF. Further research into how information-provision in IVF can be improved is needed. Trial registration number: Not applicable